Production of potential bioplastic from corn starch and extracted cellulose from caulerpa lentillifera / Faten Nurallia Kamarol Arifin - Kamarol Arifin, Faten Nurallia (2020)
Articial polymers are essential in several fields of industry, especially in the packaging industry. Yet, it has an unfavaorable impact on the environment and is the reasons of accumulation of waste and utilization. Hence, the use of renewable resources, which can reduce waste dumping problems, is being studied to create biopolymer films and coatings. Seaweed and cellulose are promising natural polymers. Green seaweed, Caulerpa lentillifera is known for its richness of cellulose. This study aims to produce a bioplastic from corn starch and strengthen with cellulose as filler. The cellulose extracted from seaweed through alkali treatment and acid hydrolysis was confirmed by FTIR characterization. The bioplastic were prepared from corn starch and seaweed based cellulose by using casting method and was revealed to have tensile strength and Young’s Modulus significantly rised with the addition of cellulose. However, the elongation at break decreased. The water absorption permeability decreased in addition to cellulose due to enhanced water resistance. Based on the results obtained, the bioplastic film with 10% cellulose concentration gave the highest tensile strength and Young’s Modulus value with fine water absorption permeability. Besides, it showed good degradation property. Overall, the combination of starch and cellulose can be used as an alternative in producing bioplastics.